2011
DOI: 10.1111/j.1468-2494.2010.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Standardized extract of Syzygium aqueum: a safe cosmetic ingredient

Abstract: Syzygium aqueum, a species in the Myrtaceae family, commonly called the water jambu is native to Malaysia and Indonesia. It is well documented as a medicinal plant, and various parts of the tree have been used in traditional medicine, for instance as an antibiotic. In this study, we show S. aqueum leaf extracts to have a significant composition of phenolic compounds, protective activity against free radicals as well as low pro-oxidant capability. Its ethanolic extract, in particular, is characterized by its ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 35 publications
2
24
0
1
Order By: Relevance
“…Antioxidants which predominantly originate from phytochemicals have been reported to play an important role in the treatment of diabetes [34]. Our results also in accordance with previous report that showed high phenol content in S. aqueum leaf ethanol extracts may be the reason for its high anti-glycation activity [35]. Syzygium species are known to be very rich in flavonoids, tannins and other polyphenol derivatives [36][37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…Antioxidants which predominantly originate from phytochemicals have been reported to play an important role in the treatment of diabetes [34]. Our results also in accordance with previous report that showed high phenol content in S. aqueum leaf ethanol extracts may be the reason for its high anti-glycation activity [35]. Syzygium species are known to be very rich in flavonoids, tannins and other polyphenol derivatives [36][37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…It is found that antioxidant activity of S. caryophyllatum extracts increased proportionally to the polyphenol content with a linear relationship between DPPH values and total polyphenols 39 . The results here reported for DPPH radical scavenging are comparables and in accordance with those reported by some authors for some syzygium species extracts (S. jambolana, S. cumini, S. aqueum, S. grantum) for DPPH and other radical scavenging [40][41][42][43][44][45][46][47] . From this study, it can be inferred that S. caryophyllaum and S. densiflorum are also equally having antioxidant proprieties.…”
Section: Dpph Radical Scavenging Activitysupporting
confidence: 95%
“… 40 reported on the use of a mixture of caffeine and Nelumbo nucitera extract. Equally, Roure et al 41 reported on the effect of a mix of ingredients including the use of tetrahydroxypropylethylenediamine and Palanisamy et al 42 . used Syzgium aqueum as an activator of lipolysis.…”
Section: Discussionmentioning
confidence: 99%